2012
DOI: 10.1111/j.1469-0691.2011.03756.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of human bocavirus in Apulia, Italy

Abstract: A serological survey was performed to determine the prevalence of antibodies against human bocavirus in an Apulian population. Anti-hBoV IgG antibodies were analysed in 1206 inhabitants (age range, 1month-84years) using a standardized ELISA test based on the use of recombinant hBoV VP2 virus-like particles. In total, 1075 (89.1%) of 1206 participants (mean age 32±24.8years) displayed anti-hBoV-IgG. The seroprevalence increased significantly (p<0.0001) in children from 2-4years (64.2%) to 5-9years (96.4%). A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
4
17
1
Order By: Relevance
“…Our results was in agreement with Jiang et al, (2016) who reported that the infections almost completely confine to infants and young children also in agreement with most of the previous studies by Allender et al, (2005), Choi et al, (2006), Chow et al, (2009) and Abdel-Moneim et al, (2013). However, some authors reported that HBoV is also a frequent virus in adults with respiratory disease Guido et al, (2012) and Ghietto et al, (2012).…”
Section: Resultssupporting
confidence: 94%
“…Our results was in agreement with Jiang et al, (2016) who reported that the infections almost completely confine to infants and young children also in agreement with most of the previous studies by Allender et al, (2005), Choi et al, (2006), Chow et al, (2009) and Abdel-Moneim et al, (2013). However, some authors reported that HBoV is also a frequent virus in adults with respiratory disease Guido et al, (2012) and Ghietto et al, (2012).…”
Section: Resultssupporting
confidence: 94%
“…A serological survey performed in Italy to determine the prevalence of antibodies against human bocavirus in an Apulian population, indicate HBoV infection is ubiquitous in the general population and early acquired from preschool children (Guido et al 2012), with more than 90 % of subjects older than 4 years displaying previous exposure to HBoV. Our results support the notion that HBoV is widely circulating in the population with prevalence of human bocavirus 2 and 3, and a large number of samples containing both these species.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, acute infections can be diagnosed by antibody assays; detection of IgM, seroconversion, or an increase in IgG titer in paired serum samples and low IgG avidity are markers of an acute primary infection (8,(40)(41)(42). In addition, epidemiological information can be gathered by measuring the IgG seroprevalence in the population (9,(43)(44)(45)(46). These studies report seroprevalences of up to 100% in adults.…”
mentioning
confidence: 99%